Medical marijuana for inflammatory bowel disease: the highs and lows. (1st February 2022) - Wynne, Joshua; Kozuch, Patricia
Abstract: Increased interest in cannabis as a potential treatment and/or adjuvant therapy for inflammatory bowel disease (IBD) has been driven by patients with refractory disease seeking relief as well those who desire alternatives to conventional therapies. Available data have shown a potential role of cannabis as a supportive medication, particularly in pain reduction; however, it remains unknown whether cannabis has any impact on the underlying inflammatory process of IBD. The purpose of this review article is to summarize the available literature concerning the use of cannabis for the treatment of IBD and highlight potential areas for future study.